Disrupted Endothelial Cell Layer and Exposed Extracellular Matrix Proteins Promote Capture of Late Outgrowth Endothelial Progenitor Cells - Jing Zhao; Claudia-Gabriela Mitrofan; Sarah L. Appleby; Nicholas W. Morrell; Andrew M. L. Lever (Stem Cells International)
Late outgrowth endothelial progenitor cells (LO-EPC) possess a high proliferative potential, differentiate into vascular endothelial cells (EC), and form networks, suggesting they play a role in vascular repair. However, due to their scarcity in the circulation there is a requirement for ex vivo expansion before they could provide a practical cell therapy and it is currently unclear if they would home and engraft to an injury site. Using an in vitro flow system we studied LO-EPC under simulated injury conditions including EC activation, ischaemia, disrupted EC integrity, and exposed basement membrane. Perfused LO-EPC adhered to discontinuous EC paracellularly at junctional regions between adjacent cells under shear stress 0.7 dyn/cm2. The interaction was not adhesion molecule-dependent and not enhanced by EC activation. LO-EPC expressed high levels of the VE-Cadherin which may explain these findings. Ischaemia reperfusion injury decreased the interaction with LO-EPC due to cell retraction. LO-EPC interacted with exposed extracellular matrix (ECM) proteins, fibronectin and vitronectin. The interaction was mediated by integrins α5β3, αvβ1, and αvβ3. This study has demonstrated that an injured local environment presents sufficient adhesive signals to capture flow perfused LO-EPC in vitro and that LO-EPC have properties consistent with their potential role in vascular repair.